21-Hydroxylase Deficiency Detected in Neonatal Screening: High Probability of False Negativity in Late Onset Form - David, Jan; Hrubá, Zuzana; Vinohradská, Hana; Hedelová, Monika; Fialová, Alena; Votava, Felix (Experimental and Clinical Endocrinology & Diabetes, 2024)
Aim Despite the high sensitivity of neonatal screening in detecting the classical form of congenital adrenal hyperplasia due to 21-hydroxylase deficiency, one of the unclear issues is identifying asymptomatic children with late onset forms. The aim of this nationwide study was to analyse the association between genotype and screened level of 17-hydroxyprogesterone in patients with the late onset form of 21-hydroxylase deficiency and to quantify false negativity.Methods In the Czech Republic, 1,866,129 neonates were screened (2006–2022). Among this cohort, 159 patients were confirmed to suffer from 21-hydroxylase deficiency, employing the 17-hydroxyprogesterone birthweight/gestational age-adjusted cut-off limits, and followed by the genetic confirmation. The screening prevalence was 1:11,737. Another 57 patients who were false negative in neonatal screening were added to this cohort based on later diagnosis by clinical suspicion. To our knowledge, such a huge nationwide cohort of false negative patients has not been documented before.Results Overall, 57 patients escaped from neonatal screening in the monitored period. All false negative patients had milder forms. Only one patient had simple virilising form and 56 patients had the late onset form. The probability of false negativity in the late onset form was 76.7%. The difference in 17-hydroxyprogesterone screening values was statistically significant (p<0.001) between severe forms (median 478.8 nmol/L) and milder (36.2 nmol/L) forms. Interestingly, the higher proportion of females with milder forms was statistically significant compared with the general population.Conclusions A negative neonatal screening result does not exclude milder forms of 21-hydroxylase deficiency during the differential diagnostic procedure of children with precocious pseudopuberty.
Keywords: congenital adrenal hyperplasia; genotype; Czech Republic